Antibacterial agents applied as antivirals in textile-based PPE: a narrative review. Issue 3 (4th March 2022) - Raza, Zulfiqar Ali; Taqi, Muhammad; Tariq, Muhammad Rizwan
Abstract: Coronavirus disease (COVID-19) has badly hit human life on the globe. Although the COVID-19 infection transmits on physical closeness, yet the staff of several public and private sectors are bound to move away from their shelters and perform their mandatory duties and other social responsibilities, thus, are probable prone to face the infection, mostly through mucosal routes. Accordingly, they need obligatory respiratory protection and physical coverage especially while dealing with suspectable COVID-19 infectees. This has resulted in worldwide demand for personal protection equipment (PPE), especially with effective antiviral activity and reusability. The common PPE like face masks, gowns, aprons and gloves, etc. come under the textile range of products. To make them effective, the PPE material should be treated with a suitable antiviral agent at appropriate stage of processing. In the current scenario, the development and characterization of new antiviral agents, particularly against COVID-19, would be a time-limited job largely when the universities are closed worldwide, and the research activities have been discontinued. Henceforth, the focus of the present review is to look at some already available antibacterial and antimicrobial agents that might exhibit potential antiviral activity. Such agents could be in hand antiviral finishes for textile-based PPE against the COVID-infection. Highlights: The COVID-19 infection transmits on physical closeness. Health care staff are more venerable to face infection than anybody else. Conventional textile-based PPE fail to prevent infection due to the retention of the virus. To make them effective, the PPE should be antivirally treated. We indicate in hand antimicrobial agents that may potentially exhibit antiviral activity.